Laboratory investigation of microbiologically influenced corrosion of carbon steel in hydrotest using enriched artificial seawater inoculated with an oilfield biofilm consortium. (June 2019) - Unsal, T.; Jia, R.; Kumseranee, S.; Punpruk, S.; Gu, T.
Abstract: Microbiologically Influenced Corrosion (MIC) is a major concern in hydrotest using untreated water. The hydrotesting process itself may last only hours, but the hydrotest water is often shut in for weeks or months. This allows biofilms to grow on pipe walls, which may eventually lead to pinhole leaks after the pipeline is commissioned. This laboratory study investigated MIC in hydrotest using an oilfield biofilm consortium to inoculate enriched artificial seawater to simulate hydrotest fluid. C1018 carbon steel coupons were placed in 120 mL anaerobic vials for incubation at 37 °C for up to 60 days. Experimental results showed that sulfate reducing bacteria (SRB), general heterotrophic bacteria (GHB) and acid producing bacteria (APB) formed robust biofilms on coupons that led to a weight loss of 7.1 ± 0.3 mg/cm 2 and maximum pit depth of 33.5 μm after 60 days. Electrochemical measurements were found to be consistent with the corrosion data. Highlights: Abiotic enriched artificial seawater (EASW) is not corrosive without O2 at 37 °C. An oilfeild biofilm consortium caused MIC against carbon steel in EASW at 37 °C. Maximum pit depth is 33.5 μm and weight loss is 7.1 ± 0.3 mg/cm 2 after 60 days. Electrochemical tests corroborate corrosion pit depth and weight loss data trends.